BIOCENOSIS SAVING EFFICIENCY OF NIFUROXAZIDE DURING ACUTE ENTERIC INFECTIONS AMONG CHILDREN - A.V. Gorelov; D.V. Usenko; M.D. Ardatskaya ("Paediatrician" Publishers LLC, 2007)
The authors made a comparative efficiency evaluation of the nifuroxazide (enterofuryl) and other nalidixic acid based medications in treatment of the acute enteric infections among children. The authors determined that though they had the equal clinical efficiency (comparable terms for the couping of the disease symptoms) enterofuryl based therapy was accompanied by the activity reduction of the opportunistic pathogenic microflora (in particular, proteolytic cultures) and balance normalization of the aerobic-anaerobic microorganism populations. The application of the nalidixic acid quite on the contrary intensified the metabolic disorders among some of the patients.Key words: acute enteric infections, children, treatment, nifuroxazide, short-chain fatty acids.